Whether to abandon or continue the petroleum product price regulation in China？. (June 2022) - Fan, Wenrui; Wang, Zanxin
Abstract: Petroleum product price regulations are usually adopted to alleviate the shocks of crude oil price volatility on macroeconomy by adjusting the petroleum product price. However, the regulation can contribute to social welfare by alleviating the price shock on the one hand, but it can reduce welfare due to its price distortions on the other hand. Thus, this study assessed the net social welfare effect using a Regime-Switching Dynamic Stochastic General Equilibrium Model, so as to inform policy-makers whether to abandon or continue the regulation. The crude oil price volatility were analysed using data from June 2000 to December 2019, and impulse responses analyses were conducted to investigate the effects of the regulation on different economic indicators. Finally, the net social welfare were assessed using a social welfare loss function. It is found that the regulation is effective in alleviating the price shocks to the macroeconomy, and consequently reducing social welfare loss in a short run. Thus, while the reform of China's petroleum product pricing mechanism should be market-oriented, the regulation is economically justified for short-term implementation to deal with crude oil price volatility. The study provides policy makers with important information on the reform of petroleum product price regulation. Highlights: There are few studies on the social welfare effect of petroleum product price regulation. The transmission of price volatility is modeled and different regimes are identified. Social welfare is positively affected by the regulation in a short run. The regulation can be employed as a policy instrument for dealing with crude oil price volatility.